Changes in Speech Production in a Child With a Cochlear Implant: Acoustic and Kinematic Evidence. - Goffman, Lisa; Ertmer, David J.; Erdle, Christa (Journal of Speech, Language & Hearing Research, 2002)
A method is presented for examining change in motor patterns used to produce linguistic contrasts. In this case study, the method is applied to a child receiving new auditory input following cochlear implantation. This child experienced hearing loss at age 3 years and received a multichannel cochlear implant at age 7 years. Data collection points occurred both pre- and postimplant and included acoustic and kinematic analyses. Overall, this child's speech output was transcribed as accurate across the pre- and postimplant periods. Postimplant, with the onset of new auditory experience, acoustic durations showed a predictable maturational change, usually decreasing in duration. Conversely, the spatiotemporal stability of speech movements initially became more variable postimplantation. The auditory perturbations experienced by this child during development led to changes in the physiological underpinnings of speech production, even when speech output was perceived as accurate. Reprinted by permission of the publisher.